2018
DOI: 10.1007/s10103-018-2494-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of photobiomodulation associated with dexamethasone after sciatic nerve injury model

Abstract: To analyze the effect of photobiomodulation and dexamethasone on nerve regeneration after a sciatic nerve crushing model. Twenty-six Swiss mice were divided into the following groups: naive; sham; injured, low-level laser therapy (LLLT) (660 nm, 10 J/cm, 0.6 J, 16.8 J total energy emitted during the 28 days of radiation, 20 s, for 28 days); dexamethasone (Dex) (local injection of 2 mg/kg for 10 consecutive days); and LLLT group associated with Dex (LLLT/Dex), with the same parameters of the other groups. For n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…After the exclusion of articles published as systematic reviews, duplicated titles, inadequate titles, and abstracts, 30 articles were selected for a complete review, and only 19 articles fulfilled all the inclusion criteria. Among these articles, we highlight that the most used wavelengths were 660 nm 1,2,7,[18][19][20] and 830 nm, 2,12,21,22 the powers were 30 2,18,19,21,22 and 40 mW 5,7 and the energy densities were 4 1,3,5,23 and 10 2,5,7,13,16,19,21 J/cm 2 . Tables 1-3 describe the experimental design used in the studies selected for this review and the parameters of the LLLT and LED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of articles published as systematic reviews, duplicated titles, inadequate titles, and abstracts, 30 articles were selected for a complete review, and only 19 articles fulfilled all the inclusion criteria. Among these articles, we highlight that the most used wavelengths were 660 nm 1,2,7,[18][19][20] and 830 nm, 2,12,21,22 the powers were 30 2,18,19,21,22 and 40 mW 5,7 and the energy densities were 4 1,3,5,23 and 10 2,5,7,13,16,19,21 J/cm 2 . Tables 1-3 describe the experimental design used in the studies selected for this review and the parameters of the LLLT and LED.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 shows the models of lesions of the sciatic nerve injury used by the authors in their studies; they are as follows: a deadweight machine, 2,5,13,19,21,22 calibrated adjustable tweezer, 12,24 homeostatic tweezer, 1,3,14,23,25,26 and non-serrated homeostatic tweezer. 8,7,20,27 The literary review showed consistent and significant results in favor of photobiomodulation about sciatic nerve regeneration after crush injury, as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…To generate our experimental model, a 3‐hour IR in the mouse paw induced the disease‐causing hyperemia and edema, followed by neuropathic pain [23,26], with no signs of peripheral nerve injury at the tourniquet [27].…”
Section: Crps Type Imentioning
confidence: 99%
“…Moreover, patients suffering from this disease experience high medical and social costs related to loss of productivity and associated disability [10]. Although PBMT is a commonly used method to reduce pain, edema, and improve nerve regeneration [16,22,23]. Treatment protocol for CRPS, comparing different wavelengths, has not yet been performed, which justify the relevance of this study and analyze the effects of 660 and 830 nm wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [13,14,24,26,32,33,39,40] have evaluated the effects of different wavelengths including 660 and 830 nm on CRPS-I, and found a reported decrease in mechanical hyperalgesia [13], decreased temperature, and early functional recovery [33] in the groups treated with PBM Group 1: control (placebo), Group 2: photobiomodulation (PBM) applied to the paw with complex regional pain syndrome type I (CRPS-I) from the warm phase, Group 3: PBM applied to the paw with CRPS-I from the acute phase, Group 4: PBM applied close to the area of the region between L4 and L5 from the warm phase, Group 5: PBM applied close to the area of the region between L4 and L5 from the acute phase, Group 6: PBM applied at two points: right paw and region between L4 and L5 from the warm phase, Group 7: PBM applied at two points: right paw and region between L4 and L5 from the acute phase, 3rd: third evaluation day, 7th: seventh evaluation day, 14th: fourteenth evaluation day, 21st: twenty-first evaluation day. .…”
Section: Discussionmentioning
confidence: 99%